Geburt Leben Sterben Tod Potsdamer Vorlesungen über das Lebenswissen in den romanischen Literaturen der Welt - Ette, Ottmar (AULA, 2022)
Our own birth and death elude our conscious experience. The world's literatures give us the opportunity to access the beginning and end of a life, to represent, reflect upon, and (re)stage birth, life, dying, and death. This highly mobile configuration releases a tremendous creative energy, which this volume analyzes against the backdrop of the question of the knowledge of life.